RELATIONS BETWEEN THE VATICAN AND ALBANIA IN THE PERIOD BETWEEN TWO WORLD WARS - Lufi, Simon (European Scientific Journal, ESJ, 2014)
In most of its long history, the Albanian Catholic Church has developed relationships with most Catholic states in Italy. Furthermore she set connections with Austria. Its impact on Albania was realized through religious protectorate that lasted until 1918. Until that time, the Holy See had set a specific status in relations with the Catholic population outside Europe, or the Muslim countries. With the same status, the Holy See dealt with the Albanian Catholic population. For a predominantly Muslim country like Albania, the Vatican directive was to keep active the Catholic institutions with the help and the protection of the Italian state. Meanwhile in Albania, an aggravated climate was being outlined between the Albanian politics and Catholic Church that became apparent in the movement of Dukagjini in November 1926. He promised to begin defining the modalities for signing a Concordat, and establishing diplomatic relations with the Holy See. Later, King Zog declared a law regarding religious communities that ran into strong resistance from Catholic communities which refused to recognize it. This law was inspired by the wildest jurisdictions. The State considered the Church an illegal organization deprived of all legal rights. The King Zog said it will make changes, but he then dragged. In conclusion we can say that it wasn’t reached the signing of the Concordat between the Holy See and the Albanian State, and therefore not even diplomatic relations was established between them. Only in 1991, for the first time there are established diplomatic relations between Albania and the Vatican.